Whiplash [large type] - Dailey, Janet (Dailey, Janet. Champions, 2021)
"When Val Champion returns to the family ranch, she's ready to put her past behind her. Her dreams of an acting career have become a nightmare. But once she sees rodeo man Casey Bozeman, she knows she's no safer at home. Val's the woman who broke Casey's heart so hard he still feels the sting. But there's no denying Casey's still drown to the fiery beauty. And there's no way he can stand by when the high stakes Professional Bull Riding finals bring out the danger Val's been running from. Suddenly the rugged cowboy is willing to risk it all for her, even if it means facing down those secrets lurking in her unforgettable eyes"--Page 4 of cover.